2013
DOI: 10.1200/jco.2013.50.3409
|View full text |Cite
|
Sign up to set email alerts
|

Solid Tumors After Chemotherapy or Surgery for Testicular Nonseminoma: A Population-Based Study

Abstract: A B S T R A C T PurposeIncreased risks of solid tumors after older radiotherapy strategies for testicular cancer (TC) are well established. Few population-based studies, however, focus on solid cancer risk among survivors of TC managed with nonradiotherapy approaches. We quantified the site-specific risk of solid cancers among testicular nonseminoma patients treated in the modern era of cisplatin-based chemotherapy, without radiotherapy. Patients and MethodsStandardized incidence ratios (SIRs) for solid tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 57 publications
8
70
2
4
Order By: Relevance
“…Prior studies have established strong dose-response relationships between cumulative cisplatin dose and secondary leukemia, and analytic investigations of solid tumor risk are needed (27,28). Fung et al showed that 3-fold increased risks of kidney cancer follow chemotherapy for testicular cancer (29), and in this regard, it is noteworthy that increased urine concentrations of Pt have also been observed for several decades after platinum administration [reviewed in (1)]. …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have established strong dose-response relationships between cumulative cisplatin dose and secondary leukemia, and analytic investigations of solid tumor risk are needed (27,28). Fung et al showed that 3-fold increased risks of kidney cancer follow chemotherapy for testicular cancer (29), and in this regard, it is noteworthy that increased urine concentrations of Pt have also been observed for several decades after platinum administration [reviewed in (1)]. …”
Section: Discussionmentioning
confidence: 99%
“…As such, firm conclusions regarding the impact of different therapeutic strategies on RS cannot be drawn. Particularly, patients treated with surgery alone might not be at increased risk of cardiovascular disease or second malignant neoplasms (2,6) and are likely to have a higher RS.…”
Section: Discussionmentioning
confidence: 99%
“…There could be an innate susceptibility for other diseases among TGCT patients, perhaps different from patients with malignant melanoma and even between seminomas and nonseminomas. CT scans traditionally used in the follow-up may have increased the risk of conditions such as second malignant neoplasms (2,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nadciśnienie tętnicze, zaburzenia lipidowe, otyłość, zaburzenia metabolizmu glukozy, ryzyko incydentów sercowo-naczyniowych czy zmniejszenie masy kostnej [34], -zwiększone ryzyko nowotworów indukowanych leczeniem (second malignant neoplasm, SMN) -ryzyko litego SMN jest tym większe, im w młodszym wieku było zastosowane leczenie nzj (chemioterapia i/lub radioterapia). Współcześnie stosowana chemioterapia z użyciem cisplatyny jest związana z 40-procentowym wzrostem ryzyka zachorowania na lity SMN [35]. Po zakończeniu chemioterapii opisywane jest również zwiększone ryzyko wystąpienia białaczek, głównie ostrej białaczki szpikowej.…”
Section: Podsumowanieunclassified